Abraham Lincoln - Griffith, D. W. (David Wark), 1875-1948; Huston, Walter, 1884-1950; Merkel, Una, 1903-1986; D.W. Griffith, Inc.; Feature Productions, Inc.; Cinetel Films ([Los Angeles, CA] : D.W. Griffith Productions : Feature Productions, 1930)
An episodic biography of the 16th President of the United States focusing on Lincoln's personal tragedies as well as his great accomplishments.
Released by Artcinema Associates Inc.
Walter Huston, Una Merkel, W.L. Thorne, Lucille La Verne, Helen Freeman, Otto Hoffman, Edgar Deering, Russell Simpson, Charles Crockett, Kay Hammond, Helen Ware.
Continuity and dialogue, Stephen Vincent Benet and Gerrit Lloyd; photography by Karl Struss; editor, James Smith; music, Hugo Riesenfeld.
English or dubbed Spanish soundtrack.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 29, 2015)
Keywords: Lincoln, Abraham, -- 1809-1865 -- Drama; Presidents -- United States -- Drama; Biographical films; Historical films; Internet videos; Feature films; Streaming video